Quadruple Helix Model Philosophy to Enhance Corporate Social Responsibility (CSR) Creativity - Achmad Akmalluddin; Suryo Ediyono (PT Mattawang Mediatama Solution, 2023)
This study explains and analyzes how the Quadruple Helix model improves Corporate Social Responsibility (CSR) creativity. Government, industry, academia, and society collaborate on innovation and development under the Quadruple Helix paradigm. This strategy lets stakeholders collaborate to boost CSR's beneficial impact. The Quadruple Helix model in CSR is examined using ontological, epistemological, and axiological methods. This study analyzes CSR, the Quadruple Helix model, and scientific philosophy literature. This study found that the ontological approach examines CSR stakeholders' reality and interactions. The epistemological method examines how entities collaborate to learn about CSR. The axiological method evaluates CSR initiatives for fairness, sustainability, and social relevance. The Quadruple Helix CSR methodology can boost innovation and effect. Government, industry, academia, and society may collaborate and innovate to create more holistic and sustainable CSR solutions. Understanding the Quadruple Helix model's CSR philosophy. This study shows that collaborative and multidisciplinary approaches improve CSR creativity and effectiveness. More research is needed to confirm these findings.